Pengembangan Modul Ajar P5 Berbasis Pendekatan Saintifik Sebagai Penguatan Karakter Siswa di Sekolah Dasar - Windi Asmawati; Sukardi Sukardi; Siti Istiningsih (Postgraduate, University of Mataram, 2025)
This study aims to develop a P5 teaching module integrated with a scientific approach in strengthening the character of students in elementary schools. The research method used is Research and Development (R&D) with a Design Based Research (DBR) development model with four stages: preliminary study, design and product development, interactive testing cycle and reflection on refinement. The sampling technique uses purposive sampling. Data collection techniques use observation, interviews, and questionnaires. Data processing techniques use descriptive statistics. Stages 1 and 2, the problem analysis and design and product development stages involve fourth-grade teachers of SD Negeri 2 Santong. Stage 3, validation involves 3 experts, namely design, material, and language experts. Stage 4, reflection and product refinement involve fourth-grade students of SD Negeri 2 Santong. The results of the study show that the P5 teaching module based on a scientific approach meets the eligibility criteria with a feasibility percentage of 88% from design experts with feasible criteria, 80% from media experts with feasible criteria, and 94% from language experts with very feasible criteria. The results of statistical testing using the T test obtained a significance value of 0.00 < 0.05, which indicates that there is a significant difference between the pretest and posttest results, while the effectiveness criteria obtained a value of 62.21% with a moderate category in improving the character of fourth grade students at SD Negeri 2 Santong.